The Effect of the KWL (Know, Want, Learn) Learning Strategy on Fourth-Grade Elementary School Students’ Understanding of Science Concepts - Firdha Dwi Maryani; Muhamad Khozinul Huda; Susilawati Susilawati (Journal of Educational Sciences, 2026)
Science learning requires strategies that help students connect prior knowledge, questions, and learning outcomes so that concepts are not merely memorized. This study aims to analyze the effect of the Know, Want, Learn (KWL) strategy on the understanding of science concepts related to energy and its transformations. The study used a quantitative approach with a quasi-experimental design of the nonequivalent control group type. The sample consisted of 44 fourth-grade students at SDN 1 Trusmi Wetan. Data collection instruments included a 20-item multiple-choice test, observation sheets for teacher and student activities, and documentation. The analysis included descriptive statistics, the Shapiro-Wilk test, Levene’s test, N-Gain, and the independent samples t-test. The average N-Gain for the experimental class was 0.7686 and for the control class was 0.5153. Hypothesis testing yielded t = 6.634 with p < 0.001. These results indicate that, in this study sample, the class that used the KWL strategy demonstrated a higher increase in science concept understanding compared to the control class. This study used a quasi-experimental nonequivalent control group design without individual randomization; therefore, the results must be interpreted carefully, taking into account the limitations of the design and the scope of the sample, which included only one school.